PENGARUH MODEL EVERYONE IS A TEACHER HERE DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SEJARAH INDONESIA - Pratama, Rinaldo Adi; Ibrahim, Nurzengky; Sarkadi, Sarkadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This research aims to find the influence of the learning model Everyone Is A Teacher Here and Self-Regulated Learning towards of Learning Outcomes ofIndonesiaHistory. The research was conducted at SMAN 8 Tangerang on the academic year 2017/2018. The research method useexperiment, with treatment by level 2X2. The results showed, as a whole, the students who were treated with the Everyone Is A Teacher Here model showed high learning outcomes, when compared to those who were given direct model learning; groups of students who have high self-regulated learning and they receive learning Everyone Is A Teacher Here has a higher learning outcomes in Indonesian history compared to those given direct learning; groups of students who have low Self-Regulated Learning and they receive direct learning, have higher learning outcomes in Indonesian history compared to those studied Everyone Is A Teacher Here; and, ultimately, there is an interaction effect between the learning model and the Self-Regulated Learning of the learning outcomes of Indonesian history.